2014
DOI: 10.1016/j.ijheatmasstransfer.2013.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of boiling heat transfer in water using a free-particles-based enhancement technique

Abstract: Enhancement of pool boiling heat transfer in water by means of the introduction of free particles on the heated surface is investigated. The layer of loose particles on the heated surface is free to move and deform under the action of bulk liquid convection and vapor nucleation. High-speed visualizations show that bubble nucleation preferentially occurs at the narrow corner cavities formed between the free particles and the heated surface. The effects of the number and size of the free particles are experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
6
1
Order By: Relevance
“…The results obtained in the present study for the wetting fluid FC-72 differ from the behavior observed with water in a companion paper [38]. While the trend of variation with particle size is similar, the optimum particle size at which the nucleate boiling heat transfer coefficient is maximized is significantly smaller for FC-72, on the order tens of microns.…”
Section: Effect Of Working Fluid Propertiescontrasting
confidence: 79%
See 1 more Smart Citation
“…The results obtained in the present study for the wetting fluid FC-72 differ from the behavior observed with water in a companion paper [38]. While the trend of variation with particle size is similar, the optimum particle size at which the nucleate boiling heat transfer coefficient is maximized is significantly smaller for FC-72, on the order tens of microns.…”
Section: Effect Of Working Fluid Propertiescontrasting
confidence: 79%
“…Thus, smaller cavities would be expected to be preferred for nucleation in FC-72. Based on the results of the present study and those in [38], it is found that the effect of wetting holds true for the free particle technique, for which narrow corner cavities formed between the free particles and the heated surface serve as nucleation sites.…”
Section: Effect Of Working Fluid Propertiessupporting
confidence: 56%
“…The mechanism by which heat transfer is enhanced upon the addition of free particles during pool boiling is by creation of surface cavity geometries that are favorable for vapor nucleation [28,29] The parametric effects of free-particle size on pool boiling performance are investigated with particle diameters ranging from 45 µm to 1000 µm and compared against the polished surface baseline case; layer thickness is maintained at a constant value of 4.8 particle diameters for all cases. The boiling curves obtained are shown in Figure 4.…”
Section: Free-particle Coatingmentioning
confidence: 99%
“…As distinct from the techniques discussed above, the placement of loose copper particles on a heated surface has been recently explored as a technique for pool boiling heat transfer enhancement by Kim et al [28,29]. This free-particle technique utilizes copper particles that are not attached to the heated surface to provide additional nucleation sites during pool boiling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation